New species and subspecies of Calamus (Arecaceae) from Vietnam - Henderson, Andrew; Dung, Nguyen Quoc (Phytotaxa, 2018)
Five new species and one new subspecies of Calamus (Arecaceae) from Vietnam are described and illustrated and compared with similar species.